Treatment patterns and survival in patients with small cell lung cancer in Taiwan. Issue 8 (28th June 2021) - Chiang, Chi-Lu; Hsieh, Wen-Ting; Tang, Chao-Hsiun; Sheu, Mei-Ling; Chen, Yuh-Min
Abstract : Background: Small cell lung cancer (SCLC) is the most aggressive form of lung cancer. The chemotherapy regimens and their efficacy in practice are seldom reported. We aimed to investigate treatment patterns and survival outcomes of patients with SCLC in Taiwan. Methods: Patients newly diagnosed with SCLC from 2011 to 2015 were identified from the Cancer Registry database. Their clinical characteristics, treatment regimens, and survival status were obtained from National Health Insurance Research database. The Kaplan–Meier method and Cox-proportional hazard model were used to analyze the survival outcomes. Results: Among a total of 2707 patients enrolled, 439 were in the limited stage (LS, 16.22%) and 2268 were in the extensive stage of the disease (ES, 83.78%). The median age was 66 and the majority were male (90.36%). The first-line regimen used for the patients was etoposide/cisplatin-based treatment, followed by etoposide/carboplatin-based regimen, and etoposide only. The median overall survival (OS) was 16.92 months (95% confidence interval [CI] 15.31–18.92) and 8.71 months (95% CI 8.38–9.07) in LS and ES patients, respectively. Chemotherapy regimen, Eastern Cooperative Oncology Group performance status, and history of radiotherapy were significant factors associated with OS. On the other hand, the major second-line treatment was a topotecan-based regimen (68.3%). However, this showed inferior survival outcome compared to etoposide-based regimen (5.09 months [95% CI 4.76–5.62] versus 8.77 months [95% CI 6.31–11.89], p < 0.001). Conclusion: Etoposide is the preferred and superior first-line chemotherapy regimen in combination with platinum, and an alternative choice of second-line regimen for Taiwanese patients with SCLC.